Characterization of Ocular Blood Flow Dysregulation Due to Carotid Artery Stenosis Using Laser Speckle Flowgraphy - Kulothungan, Gayathiri (Universiti Teknologi PETRONAS, 2021)
Carotid stenosis is caused by a build-up of plague in carotid arteries which carry oxygenated supply of blood to the brain. The narrowing of carotid arteries could eventually lead to a blockage. As the eye provides a direct access to our circulation, the ocular images offer a promising window to assess the severity of stenosis and thus predict the likelihood of a stroke attack. This study aims to analyse and compare longitudinal time difference in pulse waveform criterions of ocular blood flow (OBF) between right eye as well as left eye, under common carotid artery stenosis. Information regarding vessel condition impairment can be derived by characterizing OBF impairment. Laser speckle flowgraphy (LSFG) is used to examine the pulse wave parameters of OBF, such as resistive index (RI), acceleration time index (ATI), flow acceleration index (FAI), falling rate (FR), rising rate (RR), blowout score (BOS), blowout time (BOT), mean blur rate (MBR) and the difference in the value of MBR at maximum and minimum point (MBRmax – MBRmin, AC) within the region of optic nerve head (ONH) vessel, tissue and overall.